The Karaim translation of the Book of Nehemia copied in the 17 th century’s Crimea and printed in 1840/1841 at Gözleve, on the copyist of the manuscript, and some related issues - Shapira, Dan (Karaite Archives, 2013)
In this article, the author describes the nature of the 1840/1841 Turkic Karaim translation of the Bible, published at Gözleve / Jevpatorija, and especially, the translation of Nehemia, the last book in this publication. The author tries to identify the translator / copyist of Nehemia, who was working on the MS in 1672 in Mangup,having been based himself on the colophon, and surmised that the rest of the Bible translation may come from a MS copied by the same copyist. The author further speculates why the publisher of the Gözleve edition chose this particular MS. In order to define the Turkic language of the translation, the author goes in details about the earlier Jewish – both Rabbanite and Karaite – population of Çufut-Qal‘eh in the Crimea; his conclusion is that the earlier population was mostly immigrants from the North (the Duchy of Lithuania) and their language could not be originally any sort of Crimean Turkic. In the article, the author publishes and republishes different Judeo-Turkic Karaite Biblical translations and tombstone inscriptions.